“Home Spa” Project – Change of Children’s Knowledge and Skills after Participating in the Project - Kopek-Putała, Wioleta; Nodzyńska, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The subject of the research was to check whether students’ knowledge and skills regarding cleaning products and cosmetics will increase as a result of their participation in the 4-hour- long project entitled the “Home Spa”. For this purpose, research was conducted before and after the “Home Spa” classes, on 65 aged 7-10. As part of the laboratory, students studied the physicochemical characteristics of soaps and cosmetics received from available food products. A practical summary of children’s activities was a box full of cosmetics, while the theoretical added value was the increase in students’ knowledge of the chemicals present in their daily lives. The article discusses only part of the research on the physico-chemical properties of soap. Research results show that the hypothesis - “Home Spa“ project will increase students’ knowledge of soap properties’ - has been confirmed. But the increase in does not seem sufficient. It seems that the most important achievement of the project is the satisfaction of students with this kind of activity.